2014
DOI: 10.1051/0004-6361/201322596
|View full text |Cite
|
Sign up to set email alerts
|

A MALT90 study of the chemical properties of massive clumps and filaments of infrared dark clouds

Abstract: Context. Infrared dark clouds (IRDCs) provide a useful testbed in which to investigate the genuine initial conditions and early stages of massive-star formation. Aims. We attempt to characterise the chemical properties of a sample of 35 massive clumps of IRDCs through multi-molecular line observations. We also search for possible evolutionary trends among the derived chemical parameters.Methods. The clumps are studied using the MALT90 (Millimetre Astronomy Legacy Team 90 GHz) line survey data obtained with the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
86
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(107 citation statements)
references
References 137 publications
(270 reference statements)
21
86
0
Order By: Relevance
“…Our column density of N 2 H + ranges from 9.0 × 10 12 to 1.8 × 10 14 cm −2 , with an average of 6.3 × 10 13 cm −2 . This value is consistent with that derived by Miettinen (2014) and is also very similar to that of Sakai et al (2008). The top panel of Figure 5 shows column densities of N 2 H + versus those of H 13 CO + .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our column density of N 2 H + ranges from 9.0 × 10 12 to 1.8 × 10 14 cm −2 , with an average of 6.3 × 10 13 cm −2 . This value is consistent with that derived by Miettinen (2014) and is also very similar to that of Sakai et al (2008). The top panel of Figure 5 shows column densities of N 2 H + versus those of H 13 CO + .…”
Section: Discussionsupporting
confidence: 89%
“…Sanhueza et al (2012) found no clear evolutionary trends for C 2 H column densities and abundances in their sample of IRDCs. On the other hand, Miettinen (2014) found that both the mean and median values of the C 2 H abundance are higher towards IR-dark clumps than towards IR-bright clumps, indicating C 2 H tend to trace the cold gas. More observations should be carried out to study C 2 H in massive star formation regions.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…These indicate that Clump 4 is possibly at a later evolutionary stage as compared Clump 3 (Miettinen 2014;Yu & Wang 2015;Yu & Xu 2016). The radio peaks A and B fall within Clump 4 with B being close to the peak in the Herschel column density map.…”
Section: Molecular Line Emission Towards Cs51mentioning
confidence: 70%
“…Of the 16 molecular-line transitions covered in the MALT90 survey, only five molecular species (C2H, HCN, HCO + , HNC, and N2H + ) are detected towards these two clumps. The details of the transitions taken from Foster et al (2011) and Miettinen (2014) are listed in Table 7. Both the papers, especially the latter, give a nice review on the environment in which these molecules exist and the physical conditions required for their formation.…”
Section: Molecular Line Emission Towards Cs51mentioning
confidence: 99%